DIELECTRIC COATINGS AND THEIR EFFECT ON CORROSION PROTECTION OF THE OUTER SURFACE OF UNDERGROUND PIPELINES - V. G. Kiselev; E. N. Ruzich (Известия высших учебных заведений: Проблемы энергетики)
This paper presents comparative analysis of influence of main factors, determining characteristics of dielectric coatings, both on the corrosion of underground metal pipelines and on their cathodic protection. At the same time, it was identified that, as a priority approach in the development of coatings to protect pipelines in the ground (without the use of cathodic protection), it is necessary to choose to reduce the electrical conductivity of the coatings as a result of their saturation with soil electrolyte. This measure significantly reduces the efficiency of corrosion elements that are likely to occur when dielectric coating is damaged. As for priority in the development of coatings for combined protection of pipelines in the ground, it is necessary to increase the mechanical strength of coatings and to implement a set of measures to prevent the formation of insulation defects and to eliminate them. Actions taken in this direction significantly reduce the amount of protective current necessary for active corrosion protection of underground metal structures.